The languages of Joyce : selected papers from the 11th International James Joyce Symposium Venice 1988 - Bosinelli Bollettieri, Rosa Maria; Marengo, Carla; Boheemen, Christine van (John Benjamins Pub. Co., 1992)
The papers collected in this volume capture some of the excitement of the 11th International James Joyce Symposium, held in Venice and Trieste, June 1988. 'The contents of this book are by no means as restrictive as the title might suggest. The contributors explore not only Joyce's 'languages' and modes of communication and meaning, but, as well, concepts of significance and communication in broader contexts. Through Joyce, the writers explore and develop their own approaches and theories about language and languages, about semiotics and understanding. And about psychology, gender, physiology.